Hambatan Dan Upaya Meningkatkan Ekspor Udang Di Indonesia - Satrio, Robby; Irfani, Yusril Naufal; Lasut, Muhammad Raffii Suryansyah (Lembaga Publikasi Ilmiah Nusantara, 2023)
Indonesia, a nation with a maritime focus, has vast seas and extensive coastlines, making fisheries crucial for economic growth. Despite being a significant global fishery producer, Indonesia faces challenges in adding value to its fisheries. This study focuses on shrimp, a key export commodity, examining obstacles and strategies for improving Indonesia's shrimp export performance. Using descriptive analysis and data from the Ministry of Maritime Affairs and Fisheries, as well as online scholarly sources, the research reveals that shrimp significantly contributes to Indonesia's fishery exports. However, challenges such as limited availability of superior shrimp seed, high feed prices, environmental issues, and foreign shrimp seed competition impact shrimp farming. The study outlines positive trends in Indonesia's fishery export performance, with a substantial surplus in 2021. Shrimp dominates both export volume and value. Although the growth trend is positive, the research identifies impediments, including production challenges and non-tariff barriers. To overcome these issues, strategies must address technological, socio-economic, and environmental sustainability in shrimp farming. Government initiatives, such as tariff reductions and bilateral agreements, are essential for maximizing Indonesia's shrimp export potential. The research concludes by emphasizing the need for a holistic approach to ensure the sustainability and competitiveness of Indonesia's shrimp industry in the global market.